2008
DOI: 10.3171/foc/2008/24/3-4/e9
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the balance: cell-based therapeutics as modifiers of the amyotrophic lateral sclerosis–specific neuronal microenvironment

Abstract: ✓ Recent advances in the laboratory have improved the current understanding of neurobiological mechanisms underlying the initiating events and pathological progression observed in amyotrophic lateral sclerosis (ALS). Whereas initial studies have revealed the late-stage intracellular cascades contributing to neuronal dysfunction and cell death, more recently collected data have begun to elucidate the presence and importance of a “non–cell autonomous” component indicating that affected glial cell subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 125 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…Although motor neuron replacement is possible, this treatment strategy should take into account the multifocal motor neuron degeneration and death [6] . The roles of cell-based therapeutics might be more practical “as modifiers of the ALS-specific microenvironment” [7] or serving to “detoxify the local environment around dying motor neurons” [8] , therefore providing protection for motor neurons and retarding disease progression. Neuroinflammation, comprised mainly of astrocyte and microglial activation, is a central feature in ALS, and directly contributes to neuronal death [9] [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Although motor neuron replacement is possible, this treatment strategy should take into account the multifocal motor neuron degeneration and death [6] . The roles of cell-based therapeutics might be more practical “as modifiers of the ALS-specific microenvironment” [7] or serving to “detoxify the local environment around dying motor neurons” [8] , therefore providing protection for motor neurons and retarding disease progression. Neuroinflammation, comprised mainly of astrocyte and microglial activation, is a central feature in ALS, and directly contributes to neuronal death [9] [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cell-based therapies have emerged as potential treatments for sevtion of upper and lower motor neurons and corresponding motor and respiratory dysfunction. Approximately eral neurological disorders including ALS (18,28). For example, Xu et al (34) reported that spinal grafting of 10% of patients have an inherited form of the disease, and of these 20% carry a mutation in the superoxide human spinal stem cells (hSSCs) to the lumbar spinal cord of G93A SOD1 rats delayed the onset and progresdismutase 1 (SOD1) gene.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the discovery of several putative mechanisms underlying the onset and progression of ALS, there are no therapeutic strategies that successfully modify disease progression or outcome (33). Recently, cell-based therapies have emerged as potential treatments for several neurological disorders including ALS (18,28). For example, Xu et al (34) reported that spinal grafting of human spinal stem cells (hSSCs) to the lumbar spinal cord of G93A SOD1 rats delayed the onset and progression of disease, while also extending the life span by more than 10 days.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, stem cell transplantation has been proposed as a promising therapeutic strategy in neurological disorders 2, 3. In superoxide dismutase 1 (SOD1) mutant ALS mice, this approach, using bone marrow cells (BMCs), has been found to modify the microenvironment of the nervous system by generating microglia and glial cells,4–6 slowing disease progression and increasing survival 7…”
mentioning
confidence: 99%